Dendritic cells expressing transgenic galectin-1 delay onset of autoimmune diabetes in mice - Perone, M.J. (2006)
Type 1 diabetes (T1D) is a disease caused by the destruction of the β cells of the pancreas by activated T cells. Dendritic cells (BC) are the APC that initiate the T cell response that triggers T1D. However, DC also participate in T cell tolerance, and genetic engineering of DC to modulate T cell immunity is an area of active research. Galectin-1 (gal-1) is an endogenous lectin with regulatory effects on activated T cells including induction of apoptosis and down-regulation of the Th1 response, characteristics that make gal-1 an ideal transgene to transduce DC to treat T1D. We engineered bone marrow-derived DC to synthesize transgenic gal-1 (gal-1-DC) and tested their potential to prevent T1D through their regulatory effects on activated T cells. NOD-derived gal-1-DC triggered rapid apoptosis of diabetogenic BDC2.5 TCR-transgenic CD4+ T cells by TCR-dependent and -independent mechanisms. Intravenously administered gal-1-DC trafficked to pancreatic lymph nodes and spleen and delayed onset of diabetes and insulitis in the NODrag1 -/- lymphocyte adoptive transfer model. The therapeutic effect of gal-1-DC was accompanied by increased percentage of apoptotic T cells and reduced number of IFN-γ-secreting CD4+ T cells in pancreatic lymph nodes. Treatment with gal-1-DC inhibited proliferation and secretion of IFN-γ of T cells in response to β cell Ag. Unlike other DC-based approaches to modulate T cell immunity, the use of the regulatory properties of gal-1-DC on activated T cells might help to delete β cell-reactive T cells at early stages of the disease when the diabetogenic T cells are already activated. Copyright © 2005 by The American Association of Immunologists, Inc.